2019
DOI: 10.1186/s12938-019-0668-8
|View full text |Cite
|
Sign up to set email alerts
|

An on-line processing strategy for head movement interferences removal of dynamic brain electrical impedance tomography based on wavelet decomposition

Abstract: Background Head movement interferences are a common problem during prolonged dynamic brain electrical impedance tomography (EIT) clinical monitoring. Head movement interferences mainly originate from body movements of patients and nursing procedures performed by medical staff, etc. These body movements will lead to variation in boundary voltage signals, which affects image reconstruction. Methods This study employed a data preprocessing method based on wavelet decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The results showed that SPR could improve brain EIT image quality and recover intracranial perturbations from certain incorrect measurements [129]. In addition, the FMMU group proposed an online strategy to manage head movement interference in brain EIT data based on the distribution characteristics of wavelet coefficients [130]; the strategy reduced movement interference in the data and improved the quality of the reconstructed images.…”
Section: Reconstruction Algorithmsmentioning
confidence: 99%
“…The results showed that SPR could improve brain EIT image quality and recover intracranial perturbations from certain incorrect measurements [129]. In addition, the FMMU group proposed an online strategy to manage head movement interference in brain EIT data based on the distribution characteristics of wavelet coefficients [130]; the strategy reduced movement interference in the data and improved the quality of the reconstructed images.…”
Section: Reconstruction Algorithmsmentioning
confidence: 99%
“…Several methods have been proposed for ECG enhancement such as independent component analysis (ICA) [187], advanced averaging [188], [189], adaptive filtering [190], SVD [191], maximally decimated perfectreconstruction FIR filter banks [192], wavelet transform [193], [194], and nonlinear filter banks [195]. Generally, one of the foremost challenges in the ECG-based biometric system is the separation of the desired signal from several types of noise such as baseline wander, power line interference, motion artifacts, muscle noise, and other interference [196], [197].…”
Section: ) Noise and Artifactsmentioning
confidence: 99%
“…(a) Baseline wander: Baseline wander is a slow-varying artifact [196], which essentially results from the skinelectrode impedance variation that emerges in the form of a low-frequency noise merged with the ECG signal [198]. Impedance variation can manifest as a result of the individual breath, the electrode-skin contact, and smooth movements [197]. Moreover, baseline wander is a typical artifact that corrupts the recorded ECG signals and stems from respiration at frequency wandering within 0.15−0.3 Hz, which can be filtered using a standard high pass digital filter [199].…”
Section: ) Noise and Artifactsmentioning
confidence: 99%
“…Furthermore, for the case of complete electrode disconnection, Zhang et al recently conceived a weighted correlation coefficient method to test multiple problematic electrodes and employed data from grey model predictions for compensatory processing [58]. Subsequently, for partial electrode disconnection, Zhang et al proposed an online strategy based on wavelet decomposition to manage the EIT data from partially connected electrodes [59]. Conse-quently, in the future, approaches including special image algorithm and data preprocessing method to reduce the influence of body movement interferences are suggested to be used in clinical EIT application for delayed hemothorax detection.…”
Section: Perspectives For Future Clinical Applicationmentioning
confidence: 99%